Java elearning kit for dummies - Mueller, John Paul (John Wiley & Sons, 2014)
As a platform-independent, object-oriented programming language, Java helps developers write once and run anywhere. With this dynamic combination of a full-color printed book and a Dummies online interactive eLearning course, you'll find a wealth of information on the latest release of Java. Featuring both written and animated step-by-step how-tos, practice labs, helpful videos, numerous examples, and a host of Dummies hints and tips, this package makes your learning process easier.